Finding visual attention regions in videos - Ang, Kenny Wen Bin (2010)
Whenever one looks at a video or image, there are regions in these videos or images that are often more prominent than other regions. The gaze of human eye would notice these regions first before moving on to other parts in the video or image. These regions are called salient regions. In this report, a project on finding visual attention regions in videos is described.